Investigation And Design Optimization Of An Indoor Plane - Alias, Faiz Azizi Che (Universiti Sains Malaysia, 2017)
The aim of this project is to improve the performance of indoor plane that been used in the outreach program by the School of Aerospace Engineering and determine the performance of a thin camber airfoil against the flat plate airfoil to be utilised for the wing of the indoor plane. The project is carried out by doing some calculation of the differences in the performance of coefficient of lift for the thin camber airfoil compare to the flat plate airfoil. After that, the fabrication process for the wing of the thin camber airfoil is conducted to figure the best step of creating the mould and the way to cut the balsa wood. Then, the test will be done by timing the flight duration of the models and compare it with the previous layout. The outcome of the result is that the average flight duration for the model is 2 minutes which is an improvement to the previous design that could only achieve flight duration of about 1 minutes. However, the time reach does not meet the objectives of the project which is flight duration of 5 minutes. The reason due to the unreach goal is due to the limit put to maintain the dimension similar to previous design. The next step is to remove the limit like aspect ratio. Meanwhile, the result obtained from the used of thin camber airfoil show that it can improve the performance of the previous layout for the outreach program.